Investigation of the glucosinolates in Hesperis matronalis L. and Hesperis laciniata All.: Unveiling 4′-O-β-d-apiofuranosylglucomatronalin. (February 2020) - Montaut, Sabine; Read, Sharayah; Blažević, Ivica; Nuzillard, Jean-Marc; Roje, Marin; Harakat, Dominique; Rollin, Patrick
Abstract: The glucosinolate (GSL) profiles of wild-growing plants from the genus Hesperis, i.e. Hesperis laciniata All. (leaf, stem, flower, and root) from Croatia and Hesperis matronalis L. (leaf, stem, flower, seed, and root) from Canada, were established by LC-MS. During this investigation, 5-(methylsulfanyl)pentyl- (3 ), 6-(methylsulfanyl)hexyl- (4 ), 6-(methylsulfinyl)hexyl- (6 ), and 4′- α -l -rhamnopyranosyloxybenzyl- (17 ) GSLs were identified. In addition, the presence of 7-(methylsulfinyl)heptyl GSL (18 ), hydroxy-( α -l -rhamnopyranosyloxy)benzyl GSL, and of one d -apiosylated analogue of 17 were suggested. Moreover, one new GSL, 4′- O - β -d -apiofuranosylglucomatronalin (19 ) was isolated from H. laciniata (flower, steam and leaf) and characterized by spectroscopic data interpretation. Finally, we report the presence of 3, 4, 6, 19, glucosinalbin (12 ), and 4-hydroxyglucobrassicin (20 ) in H. matronalis and hypothesize the presence of glucomatronalin (13 ) and 3-hydroxy-6-(methylsulfanyl)hexyl GSL (21 ). Graphical abstract: Image 1 Highlights: Four known glucosinolates were identified in Hesperis laciniata All. Three more glucosinolates were suggested in H. laciniata. Five known glucosinolates were identified in Hesperis matronalis L. Two more glucosinolates were suggested in H. matronalis. 4′- O - β -d -apiofuranosylglucomatronalin is a new glucosinolate.